The relationship of serum asprosin level with diabetic and non-diabetic retinopathy - Atli, H.; Onalan, E.; Yakar, B.; Kaymaz, T.; Duzenci, D.; Karakulak, K.; Dayanan, R. (Verduci Publisher, 2022)
OBJECTIVE: This study was aimed at investigating the role of serum asprosin level in diabetic retinopathy pathogenesis and differential diagnosis diabetic and non-diabetic retinopathy. PATIENTS AND METHODS: The cross-sectional study was conducted between May 2021 and August 2021. A total of 21 subjects with diabetic retinopathy. 21 subjects with non-diabetic retinopathy. 21 subjects with type 2 diabetes mellitus (T2DM) without retinopathy and 21 healthy controls were included in the study. Biochemical parameters, serum asprosin, serum IL-6 and TNF-alpha levels were measured in all participants. RESULTS: Fasting blood glucose (FBG), HbA1c, HOMA-IR and LDL levels were higher in diabetic patients than non-diabetic. The blood asprosin levels were higher in the diabetic retinopathy group compared to the healthy control group (p=0.001). T2DM without diabetic retinopathy (p=0.010), and non-diabetic retinopathy group (p=0.043). There is a significant positive relationship between asprosin level and high FBG, HbA1c and HOMA-IR scores. CONCLUSIONS: Serum asprosin level is significantly increased in DRP group than others. A high asprosin level might be a risk factor for the development of diabetic complications, such as diabetic retinopathy. These findings suggest that the measurement of serum asprosin level may support clinicians in determining the risk of DRP development.
Keywords: Diabetic retinopathy; Nondiabetic retinopathy; Asprosin